Smoothened Regulates Migration of Fibroblast-Like Synoviocytes in Rheumatoid Arthritis via Activation of Rho GTPase Signaling - Peng, Wei-xiang; Zhu, Shang-ling; Zhang, Bai-yu; Shi, Yi-ming; Feng, Xiao-xue; Liu, Fang; Huang, Jian-lin; Zheng, Song Guo (Frontiers in Immunology, 2017)
Fibroblast-like synoviocytes (FLSs) acquire aggressive phenotypes characterized with enhanced migration abilities and inherent invasive qualities in rheumatoid arthritis (RA). Smoothened (Smo) is a key component of sonic hedgehog (Shh) signaling and contributes to tumor cell invasion and metastasis. The objective of this study is to investigate the role of Smo in the modulation of cell migration and explore the underlying molecular mechanism(s). FLSs were isolated from RA synovium. Shh levels were regulated by a Smo agonist (purmorphamine), Smo antagonist (KAAD-cyclopamine), or small interfering RNA targeting the Smo gene (Smo-siRNA) in RA-FLSs. Expression of Smo was detected by real-time PCR and western blot analysis. Cell migration was examined by transwell assay and activation of Rho GTPases was measured by pull-down assays. Incubation with purmorphamine resulted in a significant increase of cell migration and activation of Rho GTPase signaling compared to controls. However, treatment with KAAD-cyclopamine or transfection with Smo-siRNA suppressed migration of RA-FLSs and showed an inhibitory effect of Rho GTPase signaling. Together, these results suggest that Smo plays an important role in RA-FLSs migration through activation of Rho GTPase signaling and may contribute to progression of RA, thus, targeting Shh signal may have a therapeutic potential in patients with RA.